KIN‐4/MAST kinase promotes PTEN‐mediated longevity of Caenorhabditis elegans via binding through a PDZ domain. Issue 3 (17th February 2019) - An, Seon Woo A.; Choi, Eun‐Seok; Hwang, Wooseon; Son, Heehwa G.; Yang, Jae‐Seong; Seo, Keunhee; Nam, Hyun‐Jun; Nguyen, Nhung T. H.; Kim, Eun Ji E.; Suh, Bo Kyoung; Kim, Youngran; Nakano, Shunji; et al.
Abstract: PDZ domain‐containing proteins (PDZ proteins) act as scaffolds for protein–protein interactions and are crucial for a variety of signal transduction processes. However, the role of PDZ proteins in organismal lifespan and aging remains poorly understood. Here, we demonstrate that KIN‐4, a PDZ domain‐containing microtubule‐associated serine‐threonine (MAST) protein kinase, is a key longevity factor acting through binding PTEN phosphatase in Caenorhabditis elegans . Through a targeted genetic screen for PDZ proteins, we find that kin‐4 is required for the long lifespan of daf‐2 /insulin/IGF‐1 receptor mutants. We then show that neurons are crucial tissues for the longevity‐promoting role of kin‐4 . We find that the PDZ domain of KIN‐4 binds PTEN, a key factor for the longevity of daf‐2 mutants. Moreover, the interaction between KIN‐4 and PTEN is essential for the extended lifespan of daf‐2 mutants. As many aspects of lifespan regulation in C. elegans are evolutionarily conserved, MAST family kinases may regulate aging and/or age‐related diseases in mammals through their interaction with PTEN.